Revitalizing Local Manufacturing through Sustainable Energy Solutions - Sylvester; Peter; Nwaosa (Journal of Research in Industrial Technology and Educational Studies, 2026)
Local manufacturing in developing and emerging economies faces persistent challenges due to high energy costs, unreliable electricity supply, and dependence on fossil fuel–based systems, which undermine productivity, competitiveness and industrial growth. This study investigates the role of sustainable energy solutions in revitalizing local manufacturing by integrating renewable energy technologies, hybrid and distributed generation, energy efficiency measures and digital energy management systems. A comprehensive review of smart manufacturing practices, retrofitting strategies and policy frameworks was conducted to assess their impact on operational efficiency, cost reduction and environmental performance. Evidence-based analysis indicates that sustainable energy adoption enhances industrial resilience, reduces greenhouse gas emissions, stabilizes energy supply, and improves manufacturing competitiveness, particularly for small- and medium-scale enterprises. Policy and institutional support, including regulatory incentives, public–private partnerships and innovative financing models, is critical for facilitating large-scale adoption. The study concludes that sustainable energy solutions provide a practical and strategic pathway for industrial revitalization while contributing to broader Sustainable Development Goals, including affordable and clean energy (SDG 7), industry innovation (SDG 9) and climate action (SDG 13). Future research should focus on empirical implementation studies, region-specific energy integration models and quantitative evaluation of socio-economic and environmental outcomes to guide scalable adoption in energy-constrained manufacturing ecosystems.